Development of research related to alkali-silica reaction in concrete with recycled aggregates - Santos, M. B. (2010)
Since there is a possibility of incorporating recycled aggregates (RA) as a complement to primary aggregates (PA) in concrete production, taking advantage of construction and demolition waste, there are some questions on the durability of concrete with recycled aggregates (CRA) that need to be answered. The durability of concrete with primary aggregates only (CPA) is conditioned, among other factors, by its degradation due to alkali-silica reactions (ASR). Since the first cases of ASR in CPA were identified, this expansive reaction has been a research theme resulting in the development of prevention and mitigation methodologies and in the comprehension of the chemical reactions involved. The present paper proposes to describe the current development of a research program on ASR in CRA based on an experimental campaign involving the production of CRA with different replacement ratios of coarse PA with coarse concrete RA, the use of different cement classes, and variations on the concrete curing conditions and on the reactivity of the mixes.